2018
DOI: 10.1017/s1751731118000320
|View full text |Cite
|
Sign up to set email alerts
|

Sedation or anaesthesia decrease the stress response to electroejaculation and improve the quality of the collected semen in goat bucks

Abstract: Electroejaculation (EE) is stressful and probably painful; thus the administration of anaesthesia is recommended to decrease those negative effects. However, anaesthesia has a direct risk of provoking death, but sedation is less risky than anaesthesia. At the same time, α2-adrenergic agonists may improve semen quality. Therefore, the aim of the present study was to compare the physiological and behavioural responses indicative of stress and possibly pain, and the semen quality in electroejaculated untreated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…The decrease in physiological variables (HR, RR, and ruminal motility) following α 2 -adrenergic agonists were reported in other small ruminants such as sheep and goats [17,18] and camels [2]. By affecting the hormonal and nervous systems, α 2 -adrenergic agonists reduce HR, RR, and gastrointestinal motility [5,10,19]. The serum cortisol levels were signi cantly lower in different α 2adrenergic agonists groups than in normal saline.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The decrease in physiological variables (HR, RR, and ruminal motility) following α 2 -adrenergic agonists were reported in other small ruminants such as sheep and goats [17,18] and camels [2]. By affecting the hormonal and nervous systems, α 2 -adrenergic agonists reduce HR, RR, and gastrointestinal motility [5,10,19]. The serum cortisol levels were signi cantly lower in different α 2adrenergic agonists groups than in normal saline.…”
Section: Resultsmentioning
confidence: 78%
“…There are articles using other procedures (electroejaculator, rumenotomy, etc.) that suggest the use of anesthetics/sedatives improves the outcome they are looking for [19]. Good restraint is important to getting a producer done e ciently and correctly.…”
Section: Resultsmentioning
confidence: 99%
“…Some wild species, such as pampas dear males, vocalise during EE even under the usage of general anaesthesia (Fumagalli et al, 2015). Studies in different species have indicated that rams (Damián and Ungefeld, 2011), bucks (Abril‐Sánchez et al, 2018) and bulls (Falk et al, 2001; Whitlock et al, 2012) vocalise during EE. In bulls, breed differences were observed in the category of severe reactions to EE with Shorthorn x Hereford (SH) being more susceptible (Chenoweth & Osborne, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the response is highly species-specific. While rams and bucks frequently vocalise when EE is applied without anaesthesia Ungerfeld, 2011, Abril-Sánchez et al, 2017), vocalisations are not emitted if the animals are anaesthetised (Abril-Sánchez et al, 2018), or even subjected to epidural anaesthesia (Damián and Ungerfeld, 2010). On the other hand, pampas deer males vocalised during all the EE procedures even under general anaesthesia, and the latencies to the emission and the length and number of vocalisations were related to the voltage applied (Fumagalli et al, 2015), suggesting that anaesthesia was not able to block this response.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, EE without anaesthesia is painful (Ohl, 1993), so its application to animals raises welfare concerns. The use of general anaesthesia in rams (Orihuela et al, 2009a) or sedation in bucks (Abril-Sánchez et al, 2018) are recommended to decrease the welfare concerns.…”
Section: Introductionmentioning
confidence: 99%